2014
DOI: 10.1093/database/bau109
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-rich temporal relation identification and classification in clinical notes

Abstract: Motivation: We examine the task of temporal relation classification for the clinical domain. Our approach to this task departs from existing ones in that it is (i) ‘knowledge-rich’, employing sophisticated knowledge derived from discourse relations as well as both domain-independent and domain-dependent semantic relations, and (ii) ‘hybrid’, combining the strengths of rule-based and learning-based approaches. Evaluation results on the i2b2 Clinical Temporal Relations Challenge corpus show that our approach yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…The authors of [11] considered all consecutive pairs in a sentence or pairs with a dependency relation. The authors of [73] and [74] used the strategy proposed in [11]. Both strategies were successful, with [11] being more restrictive in terms of the number of created pairs.…”
Section: Hybrid Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [11] considered all consecutive pairs in a sentence or pairs with a dependency relation. The authors of [73] and [74] used the strategy proposed in [11]. Both strategies were successful, with [11] being more restrictive in terms of the number of created pairs.…”
Section: Hybrid Systemsmentioning
confidence: 99%
“…The authors of [11] also focused on the main events, considering pairs involving all first and last events in two consecutive sentences. The authors of [73] and [74] also used the strategy found in [11].…”
Section: Hybrid Systemsmentioning
confidence: 99%
“…In other studies, NLP has been used to model the corpus to extract characteristics that define clinical experiments. This approximation has been described as a hybrid according to the authors of [29], employing NLP to extract six types of features, such as a characteristic of pairs, dependence relations, lexical relations, WordNet relations, predicated argument and discourse relations, performed according to standard criteria. In the classification process, an F1-score of 0.61 was obtained with a support vector machine (SVM).…”
Section: Related Workmentioning
confidence: 99%
“…The authors used semantic and discourse relations and a combination between machine learning and rule based systems. In another work, D’Souza et al [109], have identified and classified temporal relations to 12 relation types rather than focusing on ‘three’ temporal relations as in the shared task, the experiments on the i2b2 corpus showed the effectiveness of the approach over the state-of-the-art 3-class classification results reported in the 2012 i2b2 challenge. The temporal relation extraction is also the process of identifying the chronological order of entities.…”
Section: Extraction Of Temporal Informationmentioning
confidence: 99%